Kinerja dan Keberlanjutan Kelompok Tani Hutan (KTH) Lebah Madu di Kabupaten Tabanan, Provinsi Bali: Kinerja dan Keberlanjutan Kelompok Tani Hutan (KTH) Lebah Madu di Kabupaten Tabanan, Provinsi Bali - Kurniawan, I Ketut Gede Intan; Suardi, I Dewa Putu Oka; Dewi, Ni Luh Prima Kemala (Universitas Duta Bangsa Surakarta, 2025)
The Forest Farmer Group (KTH) of honey bees plays a strategic role in supporting the economic development of rural communities while contributing to natural resource conservation and environmental preservation in Tabanan Regency, Bali Province. This dual role highlights the importance of KTH in community-based sustainable forest management. This study aims to evaluate the performance and sustainability level of the honey bee KTH across three key management aspects: Institutional Management, Area Management, and Business Management. Primary data were collected through in-depth interviews with key informants and focused group discussions (FGD) involving principal stakeholders engaged in forestry and beekeeping activities. Secondary data were obtained through literature reviews and various official publications. The analysis results indicate an overall sustainability score of 40.8, categorized as moderate sustainable. Specifically, the Institutional Management aspect scored 59.22 (moderate sustainable), while Area Management and Business Management scored 36.18 and 27, respectively, both classified as low sustainable. These findings suggest the need for targeted improvements, particularly in area and business management, to enhance overall sustainability.